COMPARISON ANALYSIS OF THE HEALTH OF SOE BANKS AND PRIVATE BANKS USING THE RGEC METHOD 2016-2020 PERIOD - Herry Susanto; Mas Ning Zahroh; Eprilly Ozza Permatadewi (International Journal Management and Economic, 2023)
Bank health can be interpreted as the ability of a bank to carry out banking operations normally and be able to fulfill all of its obligations properly in ways that are in accordance with applicable banking regulations. The purpose of this study was to determine the difference in the level of soundness in state-owned banks and private banks based on the Risk Profile factor using the NPL (Non Performing Loan) ratio, and LDR (Loan to Deposit Ratio), Good Corporate Governance (GCG), Earning (Rentability) using Return On Assets (ROA) ratio, and Net Interest Margin (NIM) and Capital ratios using the Capital Adequacy Ratio (CAR) during the period 2016 to 2020. The results of the study using the Independent Sample T-test and the Mann-Whitney test show that there is a significant difference in the level of bank soundness at state-owned banks and private banks only in the ratio of Capital Adequacy Ratio (CAR). As for the ratios of NPL (Non Performing Loans), LDR (Loan to Deposit Ratio), Return On Assets (ROA), Net Interest Margin (NIM) and Good Corporate Governance (GCG) ratios, there is no significant difference.